(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In the realm of language and interaction, sentences are fundamental units of expression, conveying meaning and enabling communication between people. An important aspect of sentences is their ability to communicate, which varies depending on how they are structured, their purpose, and the context in which they are used. This article explores the different types of sentences used in communication, examining their characteristics, how they are used, and their impact on effective communication. Whether they are declarative, imperative, interrogative, or exclamatory, each type of sentence plays a unique role in shaping conversations, conveying emotions, and prompting reactions. A deep understanding of these sentence types is crucial for improving communication skills, facilitating clearer exchanges, and strengthening interpersonal connections.